Los males de los nombramientos docentes: cuando las leyes no son una excusa - Bolaños González, Jimmy (2012)
This article makes a historic and legal analysis account of the last hundred years legal dispositions, upon rules that regulate public teachers hiring in Costa Rica, its advances and turnovers, aiming at guaranteeing the principles of suitability, equality of opportunities and professionalization of the teachers that work for the public education system. The non- legal origin of the problems is emphasized, but this does not happen because of different causes, such as: no politic will, institutional problems, lack of resources and, lack of a proper teacher preparation about their rights. The article proposes some administrative and ethic solutions, and also some legal changes in the operation of the Court that judges teachers claims in this matter